A qualitative study of undergraduate students' learning experience in sexology - Mayberry, Lorel (Curtin University, 2012)
This study responds to significant issues related to the problematic nature of perceptions of sexuality in Australian society. It also explores the extent to which the students’ view of sexuality can be influenced through a sexuality education programme delivered at tertiary level.An investigation of the literature, comprehensive interviews and feedback from students identifies the factors which form the perceptions of sexuality that students have by the time they reach young adulthood and enter the sexology class.The qualitative study provides insights into how higher education students extend their understanding of sexuality. These insights, elicited through the study, supports the considerable body of anecdotal evidence that has been gathered over thirty years in the award winning1 sexuality education programme at Curtin University. The study provides an understanding of the impact of sexuality education in an adult learning environment, using ethnographic methods to reveal ways in which undergraduate students perceive and interpret new knowledge acquired from formal studies.The study also illuminates how the learning strategies and content from the sexology class influence participants’ perceptions of their own sexuality and the sexuality of others. Students’ responses to the class were ascertained through reflective writing, interviews and focus groups. Participants demonstrated that they had responded to the ‘sex-positive’ approach to teaching and learning by revealing a more open-minded, less judgemental disposition, with an enhanced body image and added confidence to discuss sexual issues.The rich body of information emerging from this study can be used to enhance the development of sexuality education programmes in tertiary institutions and the wider community. The information includes the approach, processes, key content and the learning outcomes.It is hoped that the participants’ stories throughout this report will resonate with the reader. The aim of this report is to make a contribution to an important issue that has thus far received scant attention in the literature.